Peace Education in Teacher Education Programme A Suggested Curriculum - Dey, Niradhar (JOURNAL OF INDIAN EDUCATION, 2018)
The concept of Peace Education is not new, but its practice in our education system is a challenge. Global institutions like UNICEF and UNESCO have been initiated to make Peace Education a component of our school as well as Teacher Education long before. Accordingly, Indian institutions like the NCERT, NCTE, and the UGC have also tried to include Peace Education in Indian school, teacher, and higher education system. NCTE, the apex regulatory body for Teacher Education in India has recently come out with a revolutionary Curriculum Framework for all the levels of Indian Teacher Education Programmes. It is expected to have a complete qualitative revamping of Indian Teacher Education programmes if truely the curriculum will be implemented in the Teacher Education institutes. In its new resolution (January 2015), the NCTE has made a provision to integrate Peace Education as a component in the content designing of Diploma in Elementary Education (D.El.Ed.) curriculum, and has also made a provision to add Peace Education as an independent course in the list of optional courses in Bachelor of Education (B.Ed.) programme. Realising the importance of including Peace Education in Teacher Education curriculum, the author here tried to develop a curriculum of Peace Education which could help the Teacher Educators to design their curriculum for Peace Education at the Diploma, Bachelor, or at the Master level.